Physical modification plane: Cross MAC/PHY scheduling and resource allocation - Jaradat, Ahmad; Arslan, Hüseyin (Institution of Engineering and Technology, 2023)
[Abstract Not Available]
Keywords: MAC/PHY; Resource Allocation; Modification Plane